Preston lee's read & write english lesson 1 ebook 20 for arabic speakers. - Lee, Preston (Smashwords Edition, 2020)
20 interesting lessons to help the learner master English! Level: Intermediate - Students should have a basic knowledge of reading, writing and grammar. Application: Self-learning & Classroom Have fun and learn English the best way! This workbook has been written for all ages, children and adults alike. This workbook features: - 20 excellent lessons with everyday topics - 200 important words used in daily life - 20 Readings with everyday topics - 20 fun worksheets for easy learning - Commonly used grammar tenses - Step-by-step grammar development - Vocabulary words include Arabic translations The words in this book are taken from the best-selling book, Preston Lee's Beginner English 100 Lessons. A great book to be used with, Preston Lee's Conversation English Lesson 1 - 20.